Pengaruh Model Pembelajaran Kooperatif Think Talk Write Terhadap Aktivitas Belajar Biologi Siswa SMA: (The Effect Of Think Talk Write Cooperative Learning Model on Biology Learning Activities in Senior High School Students) - Try Susanti; Rita Simatupang; Dwi Gusfarenie; Rahmat Hidayat (BIODIK, 2021)
Activities are very important principles in learning process. The teaching objectives of course will be achieved if students actively try to achieve them. Student activity in the learning process causes high interaction between teachers and students. The objective of this study is to understand the effect of the think talk write cooperative learning  model  on  students activities in biology  learning  in SMA Negeri 2 Batanghari. This research is a quantitative study using true experimental-posttest only control design. The data collection instruments are observation sheets and documentation. Based on data analysis, it was obtained that the average of students learning activities from 3 meetings in the experiment class was 64.16%, the category active. While the average of student learning activities from 3 meetings in the control class was 37.70%, the category less active. Based on the calculation of the hypothesis test using the t-test, it was found that students learning activities obtained a value of t0 ≥ tt, namely 2.03 <4.31> 2.71, and the effect size of the treatment given was 1.43 with a percentage of 91.9% . It can be concluded that there is a significant influence on the use of the think talk write cooperative learning model on students activities in biology learning in SMA Negeri 2 Batanghari. Abstrak. Aktivitas merupakan prinsip atau asas yang sangat penting dalam pembelajaran. Aktivitas siswa dalam proses pembelajaran menyebabkan  interaksi yang  tinggi  antara  guru  dan  siswa. Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran kooperatif think talk write terhadap aktivitas belajar biologi siswa SMA Negeri 2 Batanghari. Penelitian ini merupakan penelitian kuantitatif dengan menggunakan desain true experimental-posttest only control design. Instrumen pengumpulan data menggunakan lembar observasi dan dokumentasi. Berdasarkan analisis data diperoleh rata-rata aktivitas belajar siswa pada kelas eksperimen dari 3 kali pertemuan adalah 64,16% dengan kategori aktif. Sedangkan rata-rata aktivitas belajar siswa pada kelas kontrol dari 3 kali pertemuan adalah 37,70% dengan kategori kurang aktif. Berdasarkan perhitungan uji hipotesis menggunakan uji t, didapatkan bahwa aktivitas belajar siswa diperoleh nilai t0  ≥ tt  yaitu 2,03 < 4,31 > 2,71, dan besar effect size perlakuan yang diberikan adalah 1,43 dengan persentase 91,9%. Hal tersebut dapat disimpulkan bahwa terdapat pengaruh yang signifikan dalam penggunaan model pembelajaran kooperatif think talk write terhadap aktivitas belajar biologi siswa SMA Negeri 2 Batanghari.